First record and potential biocontrol implication of Beauveria bassiana infecting Lema yerburyi on Vanda tricolor from Bali, Indonesia - I PUTU SUDIARTA; DEWA AYU PUTU KANIANITA SANJAYA; SHAH MAHAPATI DINARKAYA; GUSTI NGURAH ALIT SUSANTA WIRYA; I WAYAN DIKSA GARGITA; I KADEK WISMA YUDHA; IDA AYU PUTRI DARMAWATI; YUYUN FITRIANI; I MADE ARIMBAWA; DEWA GEDE WIRYANGGA SELANGGA; RINDANG DWIYANI; NOR KARTINI ABU BAKAR; YUSMIN MOHD-YUSUF (Society for Indonesian Biodiversity, 2025)
Abstract. Sudiarta IP, Sanjaya DAPK, Dinarkaya SM, Wirya GNAS, Gargita IWD, Yudha IKW, Darmawati IAP, Fitriani Y, Arimbawa IM, Selangga DGW, Dwiyani R, Bakar NKA, Mohd-Yusuf Y. 2025. First record and potential biocontrol implication of Beauveria bassiana infecting Lema yerburyi on Vanda tricolor from Bali, Indonesia. Biodiversitas 26: 5755-5762. The application of the entomopathogenic fungus Beauveria sp. for biological control has emerged as a viable solution to the problem of excessive insecticide application. Morphological and molecular identification targeting the amplification range of 500-600 bp for entomopathogenic fungal rDNA and 700 bp for insect COI. Pathogenic tests through Koch's postulates, isolated and cultured using Potato Sucrose Agar (PSA) media. The results of the identification of the orchid beetle were identified as Lema yerburyi, and the common name